2013
DOI: 10.1016/j.pscychresns.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure abnormalities and executive function in adolescents with prenatal cocaine exposure

Abstract: Children with prenatal exposure to cocaine are at higher risk for negative behavioral function and attention difficulties, and have demonstrated brain diffusion abnormalities in frontal white matter regions. However, brain regions beyond frontal and callosal areas have not been investigated using diffusion tensor imaging (DTI). DTI data were collected on 42 youth aged 14–16 years; subjects were divided into three groups based on detailed exposure histories: those with prenatal exposure to cocaine but not alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 47 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…For example, there is evidence for structural differences in the brain regions of adolescents with PCE. These brain regions are associated with difficulties in response inhibition (Lebel et al, 2013) and risk for substance use (Rando et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence for structural differences in the brain regions of adolescents with PCE. These brain regions are associated with difficulties in response inhibition (Lebel et al, 2013) and risk for substance use (Rando et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Within the pediatric literature, the Stroop Test has been used to assess executive dysfunctions in several children illness groups, including Traumatic Brain Injury (Max et al, 2013), benign focal childhood epilepsy (Kernan et al, 2012), leukemia (Kim et al, 2015), Attention Deficit Hyperactivity Disorder (Assef, Capovilla, & Capovilla, 2007;Chang, Liu, Yu, & Lee, 2012), autism (Lai et al, 2016), learning disabilities (Westendorp, Hartman, Houwen, Smith, & Visscher, 2014), as well as prenatal exposure to alcohol, cocaine and tobacco (Gautam, Warner, Kan, & Sowell, 2015;Lebel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have demonstrated a link between orienting performance and the superior longitudinal fasciculus and corpus callosum (Niogi et al , 2010, de Schotten et al , 2011, Bennett et al , 2012), and alerting performance and the right superior longitudinal fasciculus and corpus callosum (Mabbott et al , 2006, Takahashi et al , 2010, Klarborg et al , 2013). Complex attention processes (i.e., shifting and divided attention) have been associated with the cingulum bundle, superior longitudinal fasciculus and corpus callosum (Schulte et al , 2008, Kubicki et al , 2009, Salo et al , 2009, Takei et al , 2009, Schulte et al , 2012, Lebel et al , 2013, Peters et al , 2014). …”
Section: 1 Introductionmentioning
confidence: 99%